Pengaruh Pusat, Situasi dan Proses Keputusan Pembelian terhadap Kebijakan Produk serta Dampaknya pada Kinerja Usaha - Paroli Paroli (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2016)
This study was conducted to entrepreneur’s shirt screen printing in the City and County of Bandung with a sample of 253 employers. The purpose of this study to determine, assess and analyze Central Purchasing, Purchasing Situation and Purchase Decision Process Team Success Top Candidates for Public Officials attribute Shirt Campaign Against Product Policy and Its Impact on Business Performance. The research method is descriptive and verification. Descriptive method using balanced assessment of the variables of the study. Were data analysis techniques using structural equation modeling (SEM). Descriptive research results prove that, Central Purchasing, Situation Purchase, Purchase Decision Process and Product Policy and Business Performance in the category 'Not Good heading Very Good', but its achievement is still not optimal. The results verification proves that there is a positive and significant effect partially or simultaneously either directly or indirectly from the Central Purchasing, Purchasing Situation and Purchase Decision Process to Product Policy where the most dominant is the central purchasing. There is a positive and significant influence on Business Performance Product Policy.